Designing Magnetism in High Entropy Oxides. Issue 10 (11th February 2022) - Mazza, Alessandro R.; Skoropata, Elizabeth; Sharma, Yogesh; Lapano, Jason; Heitmann, Thomas W.; Musico, Brianna L.; Keppens, Veerle; Gai, Zheng; Freeland, John W.; Charlton, Timothy R.; Brahlek, Matthew; Moreo, Adriana; et al.
Abstract: In magnetic systems, spin and exchange disorder can provide access to quantum criticality, frustration, and spin dynamics, but broad tunability of these responses and a deeper understanding of strong limit disorder are lacking. Here, it is demonstrated that high entropy oxides present a previously unexplored route to designing materials in which the presence of strong local compositional disorder may be exploited to generate tunable magnetic behaviors—from macroscopically ordered states to frustration‐driven dynamic spin interactions. Single‐crystal La(Cr0.2 Mn0.2 Fe0.2 Co0.2 Ni0.2 )O3 films are used as a model system hosting a magnetic sublattice with a high degree of microstate disorder in the form of site‐to‐site spin and exchange type inhomogeneity. A classical Heisenberg model simplified to represent the highest probability microstates well describes how compositionally disordered systems can paradoxically host magnetic uniformity and demonstrates a path toward continuous control over ordering types and critical temperatures. Model‐predicted materials are synthesized and found to possess an incipient quantum critical point when magnetic ordering types are designed to be in direct competition, this leads to highly controllable exchange bias behaviors previously accessible only in intentionally designed bilayer heterojunctions. Abstract : High entropy oxides provide a previously unexplored route to designing magnetic behaviors not possible in less complex materials. Theoretical predictive models are developed and used to inform single‐crystal film synthesis to gain continuously tunable access to a full range of magnetic states—from antiferromagnetism to ferromagnetism to frustrated dynamical magnetism.